Something Old, Something New: When Gender Matters in the Relationship between Social Support and Health - Donato, Katharine M. (J Health Soc Behav, 2018)
This paper investigates how social support differentially benefits self-rated health among men and women hospitalized with heart disease. Using cross-sectional data about patients admitted to a university hospital, we examine the extent to which gender moderates effects for the frequency of contact with family, friends, and neighbors on health, and whether these effects differ between those with new vs. established diagnoses. We find that gender differentiates the effect of non-marital family contact on health but only when heart disease is newly diagnosed. When newly diagnosed, more frequent contact from family is associated with better self-rated health for women but not men. Men and women with pre-existing diagnoses benefit equally from more frequent contact with family.